2018
DOI: 10.3390/environments5100107
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Population in Sub-Saharan Africa: Energy for Four Billion?

Abstract: Sub-Saharan Africa is home to several of the world’s least developed economies. Additionally, forty percent of the nearly one billion people in this region lack access to basic electricity. There are several initiatives and programs aimed at increasing electricity access, clean cooking fuel, and renewable energy around the world. Economic development efforts have traditionally relied on increasing an economy’s use of fossil fuels. However, global climate change agreements and mitigation efforts are in direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Further, the power outage frequency ranges between daily and once in four days [9]. These occurrences have negatively impacted economic productivity while increasing costs of doing business in the region [2,3,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the power outage frequency ranges between daily and once in four days [9]. These occurrences have negatively impacted economic productivity while increasing costs of doing business in the region [2,3,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, though environmental concern exists across income levels, increased wealth usually results in increased valuation of the environment [93]. Our previous work [38], as well as Ahmed et al [94] suggested that up-front investments in RES now will prove more valuable than continuing to import cost-increasing fossil fuels. Implementation of energy into population projections remains an important area for further research.…”
Section: Discussionmentioning
confidence: 92%
“…The largest contributor to the percentage decline in these population shares is the population growth expected in Sub-Saharan Africa (from 14% in 2017 to 36% in 2100) [8]. That population growth will result in an entirely different set of development concerns [38]. This means that China is allowed 146 GtCO 2 in the 2017 population allowance and 71 GtCO 2 in the 2100 population-based allowance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations